Sejam as funções f : R → R e g : R → R tais que f (x) = 2x + 3 e g (x) = x – 2. Determine f
(g (x)).
Soluções para a tarefa
Respondido por
3
f(g(x)) =
= 2 · g(x) + 3 =
= 2 · (x - 2) + 3 =
= 2x - 4 + 3 =
= 2x - 1
socorroooocolegio:
obrigadaaa
Respondido por
2
Resposta:
. f(g(x)) = 2x - 1
Explicação passo-a-passo:
.
. Função composta
.
. f(x) = 2x + 3 e gx) = x - 2
.
. f(g(x)) = 2 . g(x) + 3
. = 2 . (x - 2) + 3
. = 2x - 4 + 3
. = 2x - 1
.
(Espero ter colaborado)
Perguntas interessantes
Psicologia,
9 meses atrás
Português,
9 meses atrás
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Matemática,
1 ano atrás
Direito,
1 ano atrás
Português,
1 ano atrás